MANAJEMEN PENINGKATAN MUTU PENDIDIKAN BERBASIS SEKOLAH - Hamzah Hamzah (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. Popular expectations of quality education in line with the demands of the business world to obtain quality workers. Thus education providers, must be able to respond to and accommodate the expectations and demands of the decision-making process to improve the quality of education. This gives confidence that the decision-making process can be used a variety of theories, perspectives and frames of reference (framework)-based school. This assumption gives the consequence that a school should be a major part in the decision-making process in improving the quality of education. While public participation is required in order to better understand education, while government has a role in determining the basic framework of education policy.Kata Kunci: Manajemen, Mutu Pendidikan, Berbasis Sekolah